Integrating innovation systems perspective and value chain analysis in agricultural research for development: implications and challenges - Anandajayasekeram, P.; Gebremedhin, Berhanu (International Livestock Research Institute, 2009)
The environment in which agricultural discovery and innovation occurs has been constantly changing with resultant significant influences on the organization and the social processes of discovery and innovation. As a result, there have been significant paradigm shifts in agricultural knowledge generation, dissemination and utilization. Currently, the knowledge generation, dissemination and utilization processes within the agricultural sector are guided by four complementary and mutually reinforcing concepts and principles: the innovation systems perspective (ISP); value chain approach; impact orientation; and research for development (R4D). Impact orientation and R4D are implicit in the concept of ISP. A major challenge confronting the agricultural research for development (AR4D) community is how to integrate these different concepts in the design, implementation and evaluation of AR4D. However, an operational model that integrates ISP and value chain approach into AR4D is lacking. This paper is an attempt to develop such an operational model. The paper also addresses the emerging issues and challenges in the integration process and its institutionalization within the broader framework of AR4D.